Hybrid Lossless Compression Techniques for English Text - Jannat Tariq; Mahmood F. Mosleh; Maha Abdulameer; Huthaifa A. Obeidat; Omar A. Obeidat (Journal of Techniques)
Since the demand for data transfer and storage is always increasing, sending data in its original form will take a long time to send and receive. Compression is an important issue for digital communications systems because it imposes an important rule while reducing complexity and power requirements. The goal of compression is to reduce the file size without compromising the quality of the information, which leads to more capacity saving and reduces the required bandwidth in terms of the communications system. This paper proposes a system that consists of a hybrid of two lossless techniques, including a concatenation of Huffman and LZ4 in order to enhance the traditional techniques. The result of the proposed system demonstrates that the proposed combination techniques reduce the file size significantly, achieving between 73.649 % and 79.708 % in terms of average saving ratio (SR). The above would give us credible, cost-effective, and affordable lossless encoding systems for electronic communication systems.